Analisis Komunikasi Digital Aplikasi Sihalal pada Pemilik UMKM di Kabupaten Serdang Bedagai - Syafruddin Pohan; Sofya Rahma Nasution; Ratna Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The government realizes that the government service system must adapt by using information communication technology that can facilitate all community activities through digital communication. One example of digital transformation in government agencies is the Sihalal application. This application is an application created by the Ministry of Religion to make it easier for UMKM business owners to obtain halal certification, as well as to help accelerate data collection of halal products. The Ministry of Religion through PPH assistants guides UMKM owners to register their products so that they can get halal certificates. The purpose of this study is not only to analyze digital communication, but also to directly analyze the application of digital communication to UMKM owners in Serdang Bedagai Regency related to the process and stages of registering business products in the Sihalal application. This research uses qualitative research methods with a descriptive approach. The results of the study found that the digital communication of the Sihalal application with the help of PPH assistants runs effectively, but there are several problem and obstacles that occur in the field such as internet network access and the long distance of PPH assistants' consultations and the registration flow in the Sihalal application which is easy to apply.